Molecular characterization of plasmids in Salmonella enteritidis phage types. - Brown, D. J. (Cambridge University Press, 1993)
Plasmids in selected type strains of 26 of the Salmonella enteritidis phage types have been characterized by restriction enzyme fingerprinting and by DNA-DNA hybridization with oligonucleotide probes for Salmonella plasmid virulence (Spv) genes. With one exception, the fingerprints of the 38 MDa plasmids studied were homogeneous but there was heterogeneity in the fingerprints of 59 MDa plasmids found in 4 of the type strains. However all 38 MDa and 59 MDa plasmids were related as was a 45 MDa plasmid identified in the type strain of phage type 19. A 3.5 kb fragment homologous to SpvC was conserved in Hind III digests of all 38 MDa and 59 MDa plasmids, and in the related 45 MDa plasmid. In contrast a 65 MDa plasmid found in the type strain of phage type 10 was not related to these three plasmid molecular weight groups and did not carry the SpvC gene.